The genetic basis of endometriosis. - Zondervan, K; Cardon, L; Kennedy, S (2001)
Family studies have long suggested a role for genetic factors in the aetiology of endometriosis. The influence of genes on disease development has mainly been researched independently of environmental factors, yet their interaction must play an important role. Greater exposure to retrograde menstruation and oestrogen is likely to increase the risk of endometriosis; toxic compounds such as dioxin may increase the risk, although the only direct evidence has come from primate studies. Previous association studies implicated GALT (a gene involved in galactose metabolism), and GSTM1 and NAT2 (genes encoding for the detoxification enzymes) as possible disease susceptibility genes. Recent findings have added to the evidence for the involvement of GSTM1 and NAT2, but have cast doubt on the role of GALT. However, the design of many genetic and epidemiological studies has been inadequate with respect to sample size, consistency in phenotype definition, and the choice of control populations. These features are likely to influence results, and could partly explain the lack of consistency in the findings. Future studies should use a consistent disease definition and be of appropriate epidemiological design.